Propagation of human prostate tissue from induced pluripotent stem cells. (14th March 2020) - Hepburn, Anastasia C.; Curry, Emma L.; Moad, Mohammad; Steele, Rebecca E.; Franco, Omar E.; Wilson, Laura; Singh, Parmveer; Buskin, Adriana; Crawford, Susan E.; Gaughan, Luke; Mills, Ian G.; Hayward, Simon W.; et al.
Abstract: Primary culture of human prostate organoids and patient-derived xenografts is inefficient and has limited access to clinical tissues. This hampers their use for translational study to identify new treatments. To overcome this, we established a complementary approach where rapidly proliferating and easily handled induced pluripotent stem cells enabled the generation of human prostate tissue in vivo and in vitro. By using a coculture technique with inductive urogenital sinus mesenchyme, we comprehensively recapitulated in situ 3D prostate histology, and overcame limitations in the primary culture of human prostate stem, luminal and neuroendocrine cells, as well as the stromal microenvironment. This model now unlocks new opportunities to undertake translational studies of benign and malignant prostate disease. : Abstract : We demonstrate for the first time that induced pluripotent stem cells (iPSCs) can generate human prostate tissue both in vivo and in vitro, overcoming some significant limitations with patient-derived xenografts and primary culture to provide a complimentary approach. Furthermore, the in vitro model provides a new platform to create a living biobank of prostate cancer organoids derived from gene editing of iPSCs for preclinical drug testing.